True detectives - Kellerman, Jonathan (New York : Ballantine Books, 2009)
When a man is hired to investigate the disappearance of twenty-year-old woman, he discovers that his estranged half-brother cop is also on the case, but only after consulting psychologist Alex Delaware do they stand any chance of success.
Originally published: New York : Ballantine Books, c2009.
Includes excerpt from: Evidence (p. [463]-474).
Keywords: Delaware, Alex (Fictitious character) -- Fiction; Psychologists -- Fiction; Missing persons -- Investigation -- Fiction; Private investigators -- Fiction; Brothers -- Fiction; Los Angeles (Calif.) -- Fiction; Mystery fiction